Demographic characteristics and pain treatments of patients applying to the algology polyclinic of Fırat university medical faculty - Elpeze, Necat; Ozcan, Sibel; Altun, Aysun Yıldız; Aksu, Ahmet; Günay, Fethi; Turkoglu, İsmail Cem (My University, 2024)
Aim: The aim of this study is to retrospectively evaluate the patients who were admitted to the Algology polyclinic with pain, focusing on their sociodemographic characteristics, types of pain, and pain management. Materials and Methods: In this study, the pain assessment forms of patients who presented to our Algology polyclinic with pain complaints between January 2022 and December 2022 were examined. The sociodemographic characteristics of the patients, pain properties, and treatments administered were retrospectively evaluated. Results: Within one-year period, a total of 2001 patients have been admitted to our clinic. 75.5% of the patients were between the ages of 15 and 64. The average age of men was found to be significantly lower than the average age of women. 71.7% of the patients were overweight or obese, with obesity being more prevalent in women. Additionally, 69.8% of the patients had at least one comorbidity, with cardiovascular disease (CVD) and diabetes mellitus (DM) being the most common. The most common causes of pain were low back pain, neck pain, myofascial pain, and knee pain. The Visual Analog Scale (VAS) score was found to be 6.64. Interventional pain treatment was applied to 53.3% of the patients, with the most common methods were caudal epidural injection, cervical epidural injection, and ozone trigger point injection. Conclusion: Close examination of patients’ responses to treatment and knowledge of sociodemographic characteristics are important. In addition to well-planned medical treatment for pain, we believe that interventional pain treatment can alleviate patients’ pain, improve their quality of life, and potentially prevent work loss due to chronic pain.
Keywords: Sociodemographic characteristics; Algology polyclinic; Interventional pain treatment